Book Review: A Digital Bundle: Protecting and Promoting Indigenous Knowledge Online - Bane, Treasa (Journal of Copyright in Education & Librarianship, 2024)
When Indigenous Knowledge is made openly available, it enables members of Indigenous communities to resist colonialism to pursue self-determination as well as cultural transformation for Indigenous Peoples and non-Indigenous Peoples alike. Jennifer Wemigwans’ A Digital Bundle: Protecting and Promoting Indigenous Knowledge Online explores what opening cultural heritage entails from an Indigenous perspective.